2021
DOI: 10.1186/s13089-021-00237-3
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasound competency assessment tool for four-view cardiac POCUS

Abstract: Background Point-of-care ultrasound (POCUS) has been recognized as an essential skill across medicine. However, a lack of reliable and streamlined POCUS assessment tools with demonstrated validity remains a significant barrier to widespread clinical integration. The ultrasound competency assessment tool (UCAT) was derived to be a simple, entrustment-based competency assessment tool applicable to multiple POCUS applications. When used to assess a FAST, the UCAT demonstrated high internal consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Such use of OSCEs is consistent with previous published reports exploring the impact of SPteachers on student learning. 7-10 Each student's performance was rated using the Ultrasound Competency Assessment Tool 16,17 to ascertain a difference in performance between the two groups following the training session. This tool was chosen because it includes an entrustment score, making ratings easily interpretable through five basic anchors 18 compatible with competency based medical education in UGME.…”
Section: Methodsmentioning
confidence: 99%
“…Such use of OSCEs is consistent with previous published reports exploring the impact of SPteachers on student learning. 7-10 Each student's performance was rated using the Ultrasound Competency Assessment Tool 16,17 to ascertain a difference in performance between the two groups following the training session. This tool was chosen because it includes an entrustment score, making ratings easily interpretable through five basic anchors 18 compatible with competency based medical education in UGME.…”
Section: Methodsmentioning
confidence: 99%
“…Through direct observation, feedback, and structured evaluation, this tool allows supervisors to assess the trainee's ability to complete a task, ranging from total intervention to independence. Results from the UCAT study revealed excellent interrater reliability between two EM faculty observers as well as a high correlation between the domain assessment and entrustment scale 9,10 …”
Section: Introductionmentioning
confidence: 94%
“…In 2020, Bell et al 9,10 created the ultrasound competency assessment tool (UCAT) to address this gap. The UCAT is based on the results of a Delphi survey of Canadian emergency physicians and was validated by having EM residents perform a focused assessment with sonography in trauma (FAST) examination.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations